Benthic macrofauna under the effect of net cage fish farming in the São Mateus River, southeastern Brazil - Rezeno, Jociane Liandro; Teodoro, Nálita Maria Scamparle; Costa, Karla Gonçalves da (Brazilian Journal of Production Engineering, 2020)
The rapid growth of fish farming in Brazil is due to the high degree of profitability and rapid return on investment. However, the choice of an unfavourable location for the implementation of network tanks can result in the production of low-quality effluents, low concentration of dissolved oxygen, high concentrations of organic matter, nutrients and suspended solids, which affect aquatic environments. In this way, the monitoring of the benthic community can be used as an environmental assessment tool, reflecting changes in the physical, chemical and ecological conditions of the place. Thus, the objective of this study was to evaluate the macrobenthic community under net cage in a stretch of the São Mateus river, ES, in order to detect possible changes resulting from this activity. Five samplings were carried out between February 2011 and May 2012, at four sampling points: under the fish tank, on the opposite marge, 500m upstream and 500m downstream. The samples were collected with a Van Veen grab and the macrofauna was quantified and identified in the laboratory. 195 individuals were found and Oligochaeta and Chironomidae were most abundant. Only temporal variations were detected. The BMWP index showed that the environmental quality of the entire study area is very critical, demonstrating that the environmental degradation of the river caused by several factors, including the release of organic effluents, seems to compromise the local benthic fauna much more than the fish farming itself.